Pengembangan Modul Ajar IPAS Berbasis Project Based Learning (PjBL) dalam Penerapan Merdeka Belajar - Nurmiati, Nurmiati; Danial, Muhammad; Arsyad, Muhammad (Program Pasca Sarjana UNM, 2023)
This research is a development research which aims to develop a valid, practical and effective IPAS teaching module based on Project Based Learning (PjBL). The development model used is the 4-D development model which consists of four stages, namely defining, designing, developing and deploying. The teaching module developed was validated by two experts, then tested on 37 students of class X Pharmacy at SMK Negeri 1 Polewali. The results of the research show that the developed module meets the criteria of validity, practicality and effectiveness. The module is said to be valid based on the results of module validation with an average value of 3.73 in the very valid category. The module is said to be practical based on (1) the implementation of the module by two observers in the learning process with a score of 1.82 in the fully implemented category; (2) the teacher's response to the developed teaching modules obtained an average score of 94 in the very practical category; and (3) student responses with an average score of 89.75 in the very practical category. The module is said to be effective based on the results of the analysis of student learning outcomes tests with a class completeness percentage of 94.59%. The developed module contains covers, initial competencies, core components, learning activities, and assessments.